Negotiating Coherent Science Teacher Professional Learning Experiences Across a University and Partner School Settings. Issue 2 (17th February 2019) - Campbell, Todd; McKenna, Thomas J.; Fazio, Xavier; Hetherington-Coy, Amy; Pierce, Patrick
ABSTRACT: This research investigates the assumptions underlying the work of a research–practice partnership (RPP) made up of university science teacher educators and mentoring science teachers. With increased attention to what have been described as significant shifts proposed in science teaching and learning connected to recent standards documents in the United States, increased attention and possibilities exist for collaborative work with in-service mentoring teachers to not only focus on professional learning connected to these standards documents but to do so in ways that can increase the coherence between science teacher education programs and the local schools that preservice science teachers find themselves navigating as they learn to teach. Drawing on the design-based research paradigm connected to conjecture mapping, this current research articulated and tested, using qualitative methods, the design conjectures underlying mentor teachers' experience within professional learning as part of the RPP. In the end, design conjectures that supported teachers to take on "learner hat" experiences in early stages of the RPP followed by engagement in curriculum codesign and implementation supported mentor teachers in beginning to reconceptualize visions of their teaching and learning while also appropriating and tuning high-leverage tools to support a focus on student ideas in science classrooms. Finally, issues related to the complexity of teacher education programs were identified for needed increased attention into the future.